Reluctance to change and end psychotherapy - John E. Berg (Mental Illness)
Reluctance to change therapy has clinical and economic implications. Therapists are expected to deliver treatment in a oneto- one setting ending up with patient improvement. Such an achievement is difficult to overview. There is great uncertainty as to what works in psychotherapies despite research efforts. Prolonged treatment duration with little positive effect may be caused by factors inherent in therapist and patient and the external environment. Two cases are discussed illustrating the need for better surveillance of what happens in the therapy room. Responsibility for the progress in therapy rests on the shoulders of the therapist. When therapy becomes detrimental to patient and therapist, we do not have a comprehensive system to interfere or help. Delayed recovery emanates as an increase in costs to society and the family. This is the case when return to work after treatment is partly or completely retarded.